Breakthroughs in immune checkpoint therapy: overcoming NSCLC immune checkpoint therapy resistance with novel techniques - Kang, Li-Ping; Huang, Hua-Jing; Xu, Cong; Chen, Hui-Hui; Huang, Dong-Hui; Jiang, Ze-Bo (Frontiers in Immunology, 2025)
Immune checkpoint therapy has emerged as a revolutionary approach in the field of non-small cell lung cancer (NSCLC), offering new hope to patients with various malignancies. Despite its success, a significant proportion of patients exhibit primary or acquired resistance, limiting the efficacy of these treatments. This review provides a comprehensive analysis of recent breakthroughs in immune checkpoint therapy, focusing on the underlying biology of immune checkpoints, current checkpoint inhibitors, and the mechanisms of resistance that challenge treatment effectiveness. In particular, we will explore novel strategies designed to overcome these resistance mechanisms, including combination therapies that enhance anti-tumor immune responses, the use of personalized neoantigen vaccines, and microbiome-modulating therapies. Additionally, we will examine the role of emerging biomarkers, such as TCR clonality and T-cell inflamed gene signatures, in predicting patient responses. By synthesizing these insights, this review aims to highlight innovative approaches that could significantly improve therapeutic outcomes for patients with NSCLC and other malignancies, ultimately advancing the field of cancer immunotherapy.